Fraud triangle dimensions on academic fraud behavior - Mulyati Akib; Ika Maya Sari; Nitri Mirosea; Rindi Ashari (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study aims to determine the effect of Dimensions of Pressure, Opportunity, and Rationalization on academic cheating behavior in accounting students in the undergraduate program at Halu Oleo University. This type of research is quantitativeresearch, using a questionnaire as a research instrument. The sampling technique used is purposive sampling. This study used 92 respondents. The data used in this study is primary data. The data obtained in the form of answers from respondents were tabulated and processed using SPSS version 25 software. The results of this study indicate that pressure and rationalization partially have a significant effect on academic cheating behavior in accounting students at the Faculty of Economics and Business, Halu Oleo University. However, partial opportunity does not have a significant effect on academic cheating behavior in accounting students from the Halu Oleo Faculty of Economics and Business. This study also shows that simultaneously the three independent variables have a significant effect on academic cheating behavior in accounting students at the Faculty of Economics and Business, Halu Oleo University.